Development of Information System-Based Policy for COVID-19 Affected Students in the Semi-Arid Area of Indonesia - Apris A. Adu; Sarci M. Toy; R. Pasifikus Christa Wijaya; Indra Yohanes Kiling (Indian Journal of Forensic Medicine & Toxicology, 2021)
This study aimed to provide an overview of the diet of students during the COVID-19 pandemic, socioeconomicstatus, the physical activities undertook the practiced COVID-19 prevention behavior, and student health.The sample size obtained was 253 participants, who were new students for the 2020/2021 academic year.Structural equation modeling was used for statistical analysis. Students could access nutritious food, but itwas not followed by regular daily exercise. Students were also found to have good COVID-19 preventionbehavior, for example using masks, washing hands, and coughing and sneezing etiquette, but only 41% ofstudents had sufficient rest or sleep.Students have a good level of health, despite lacking physical activities.COVID-19 preventive behavior and socioeconomic status indirectly had an impact on student health. Theright policies are necessary to improve student health.